Knowledge, practices and health seeking behaviour regarding dengue among household in an urban slum of Visakhapatnam, Andhra Pradesh - Konar, Amrita Kumari; Manasa, Rangala Venkata (International Journal Of Community Medicine And Public Health, 2021)
Background: Dengue/dengue hemorrhagic fever is an emergent disease in India. It is a mosquito-borne viral disease. The aim of this study is to assess the knowledge, attitude and practice regarding dengue among households in urban slum area and to find out the health seeking behavior of respondent during first episodes of fever. Methods: This study was a descriptive cross sectional study undertaken in field practice area of UHTC of GITAM institute of medical science, Visakhapatnam, Andhra Pradesh. The sampling technique was two stage simple random sampling. Face-to-face interview based on a pre-designed and pretested questionnaire. The data was compiled and analyzed. Results: Out of total 262 individual were interviewed, 69.8% were aware about dengue. The major source of information was TV/radio (74.4%). The most common health seeking behaviour for first episode of fever was nearby UHTC and then government hospital. Conclusions: The knowledge and awareness regarding dengue was satisfactory in the study population but the knowledge about the mode of transmission and breeding habit is still lacking. More awareness campaign and health education will improve.